Radiographic and Computed Tomographic Anatomy of the Donkey Carpus - Alsafy, Mohamed A.M.; El-Kammar, Mahmoud H.; Nouh, Samir R.; Abou-Ahmed, Howaida M.; Perez, William; Vazquez, Noelia; Swidan, Dina (Journal of Morphological Sciences, 2019)
Introduction Joint diseases represent most of the musculoskeletal disorders. Therefore, the aim of the current study was to make a radiographic and computed tomographic analysis of the structures of the donkey carpus and investigate carpal joint affections.Materials and Methods The study was performed with the use of cross-sectional anatomy, digital X-ray and computed tomography (CT) scans. Twelve adult donkeys were used.Results The results provide a full description of the bones and soft tissues of the carpus. The carpal joint was examined at many levels using different CT and X-ray planes. The carpus was studied through bone and soft-tissue windows that were compared with cadaver cross-sections for interpretation. The study revealed some joint affections that were detected by the CT scans but were unapparent in X-ray films, such as bony cysts, hemorrhagic bony cysts, old and microfractures, and bony sclerosis. Some normal anatomic variants were recorded during the examination of the CT scans to assist the equine practitioners that deal with the carpal joints of donkeys.Conclusion Both imaging techniques are suitable for the examination of the carpus, and the selection of the technique is conditioned to many factors, like the type of tissue affected and economic reasons, such as the availability of the apparatus and the cost of the animal.
Keywords: cadaver cross-sections; carpal joint; digital x-ray; computed tomography